Challenges faced by NPOs providing services to refugees and asylum seekers in the Cape Town Metropolitan area - Reiss, Chloé (Department of Social Development, 2016)
Non-Profit Organisations (NPOs) providing services to refugees and asylum seekers are hard-pressed to effectively address the many challenges that these individuals face. Many struggling Black South Africans perceive these migrants as competing for scarce resources or as being able to achieve better livelihoods than they have in their own country. This study examines the challenges faced by NPOs providing services to refugees and asylum seekers in the Cape Town metropolitan area. A qualitative research design was adopted and a total of twenty-one respondents from twelve NPOs were purposively targeted. Thus a non-probability sampling strategy was used. Data was collected through face-to-face in-depth interviews using a semi-structured schedule. The findings reveal that the legacy of the past and perpetuating socio-economic inequalities hinder the integration of refugees and asylum seekers in South Africa. Xenophobia remains a major concern and the approach of government toward migration appears contradictory. Documentation, administration and corruption at the Department of Home Affairs (DHA), the closure of the Cape Town Refugee Reception Office (CTRRO), abuse and discrimination, are major challenges for refugees and asylum seekers. NPOs assisting them remain constrained by lack of funding and government cooperation. Further awareness initiatives, community mobilisation and social cohesion programmes are required. These findings inspired some recommendations for further research as well as for NPOs, which include lobbying for the establishment of a Central Migrant Help Desk; enhancing access to psychological services; developing more social cohesion programmes and further facilitating access to basic social services. Other recommendations encourage NPOs to develop a policy document to present to parliament tackling the issues of backlogs, renewal of documents, regulations in the workforce, documentation awareness, improvement of professional training of stakeholders; and advocating for progressive and coherent policy-decision making.